Positional relationship detection system in which a detectable unit of a detection subject of a detector unit is provided with a plurality of detectable spots for detecting a distance from a detection reference point of the detector unit - HORII, TAKAHIRO; YAGITA, NOBUYUKI; HAYASHI, KOUTAROU; OGISU, MOTONARI (2021)
A positional relationship between an article holding portion of an article transportation vehicle and a transfer location is detected with a simpler structure. A detectable unit of a detection subject to be detected by a detector unit is provided with a plurality of detectable spots for detecting a distance from a detection reference point of the detector unit. The detectable unit is formed in a three-dimensional form as being made up of a plurality of detectable surfaces. The plurality of detectable surfaces can be detected for at least two of planar relative position, inclination, and rotating angle to correspond to the value of the distance from the detection reference point. The planar relative position indicates a relative position of the article holding portion with respect to the transfer location in a first direction on a reference plane and a second direction, which is orthogonal to the first direction, on the reference plane. The inclination is the inclination of the article holding portion with res